EVALUASI PENYUSUNAN NORMA, STANDART DAN KRITERIA PEMANFAATAN RUANG KABUPATEN KUDUS TAHUN 2010 - Fujiastuti, Asyifa; Pigawati, Bitta (Jurnal Geografi, 2014)
Norms, standard and criteria formulation for Land Utilization in Kudus Regencywas part of Land Use Activity. The standard formulation based on land suitabilitybetween land use planning that has been established with the existing land use.The criteria based on land carrying capacity that had been set in the RegionalPlanning (RTRW) by looking at trend of the most dominant land use development.The purpose of this evaluation was to see the suitability of Norms, Standards, andCriteria of Kudus Regency Land Use Planning based on evaluation indicatorsthat refer to process and outcome aspects of evaluation which refers to UUPRNo. 26 of 2007 and the Minister of Public Works Regulation No.16 / PRT / 2009.The results obtained from the evaluation: based on process, drafting of norms,standards and criteria for Kudus Regency Land Use Planning in 2010 has notbeen fully followed the formulation method that should be used as a reference,while based on results, drafting of norms, standards and criteria for KudusRegency Land Use Planning in 2010 has achieved its goal.